MODEL SOFTWARE PENDIDIKAN DALAM FORMAT TUTORIAL PERSAMAAN LINIER DUA PEUBAH - Bunyamin bunyamin (Jurnal Elektronika Telekomunikasi & Computer, 2017)
Object of the research is to create a education software in tutorial format that can solve linier equation system two variables. Research using the analysis method of analyzing a number of requirements and design a tutorial object model of object-oriented programs. The result of this study is a software package that can solve linier equation system two variables with use elimination, subtitution and determinan methods.Kata Kunci : Software, tutorial, linier Equation.